STRATEGI KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA SMA NEGERI 3 SEUNAGAN KABUPATEN NAGAN RAYA. - M. Dahlan, Cut Zahri Harun, Nasir Usman. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: The purpose of this study was to determine the program, implementation, follow-up and the obstacles faced by principals in the implementation of academic supervision in improving the professional competence of teachers. This study used descriptive qualitative approach. The technique of data collection used were observation, interviews, and documentation. Subjects of study were principals, vice-principals, teachers and supervisors. Data were analyzed with data reduction, data display, conclusion drawing and verification. The results showed that: 1) Programs are arranged at the beginning of each school year based on the results of the follow-up implementation of supervision in the previous year based on the instructions given by the Department of Education. Teachers were not fully involved in setting the programs and it was planned twice in one semester. 2) Implementation of supervision begins with socialization activities for teachers and pre-observation meeting. Supervision activities were carried out by providing guidance and direction on the preparation of learning tools, learning implementation and evaluation of learning through meetings, discussions, individual meetings and classroom observations. Principal recorded all activities on a classroom observation on instrument sheet that will be used as input and consideration for guidance in improving teachers' professional competence. 3) Follow-up is done through discussions between principals and teachers to provide feedback from the results of classroom observation. Results of follow-up were concluded with concrete steps contextually as a way out of the problems faced by teachers in the learning process and as an improvement in the future to improve the quality of learning. 4) Obstacles faced were the supervision schedule was often shifted, the use of teaching methods were still centered on the teacher, the teacher felt clumsy when supervised and teachers were less active in seeking new information about learning.Keywords: Academic Supervision and Teacher Professional Competence.Abstrak: Tujuan penelitian ini untuk mengetahui strategi perencanaan program, pelaksanaan program untuk mengaktifkan kegiatan Musyawarah Guru Mata Pelajaran (MGMP), strategi supervisi kepala sekolah dan kendala-kendala yang dihadapi kepala sekolah dalam meningkatkan profesional guru SMA Negeri 3 Seunagan Kabupaten  Nagan Raya. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data melalui: observasi, wawancara, dan dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah, guru, komite sekolah, ketua MGMP, dan pengawas. Data dianalisis dengan cara mereduksi, display, mengambil kesimpulan, dan verifikasi data. Hasil penelitian menunjukkan bahwa: (1) Program kepala sekolah disusun secara bersama-sama dengan melibatkan seluruh personel sekolah pada setiap akhir tahun ajaran melalui kegiatan rapat dewan guru. Sekolah belum membentuk tim khusus dalam pengembangan kurikulum. Program yang disusun adalah: program tahunan, program semester, langkah-langkah perencanaan pembelajaran setiap bidang studi, model penilaian, kegiatan MGMP, menyediakan dan membagikan kalender pendidikan, buku tulis, dan alat tulis. (2) Strategi kepala sekolah dalam mengaktifkan MGMP adalah dengan memberlakukan absensi, pemberian insentif, mengikut-sertakan diri sendiri dalam kegiatan kelompok kerja guru, serta akan menegur bagi guru yang tidak pernah hadir. (3) Teknik kepala sekolah dalam melaksanakan supervisi dengan cara melaksanakan kunjungan kelas, observasi dan memperbaiki kekurangan dan kelengkapan perangkat pembelajaran. Pelaksanaan supervisi tidak semuanya berdasarkan jadwal yang telah ditetapkan dan masih ada guru yang belum siap secara mental untuk dilakukan supervisi, dan (4) Kendala-kendala yang dihadapi kepala sekolah adalah menyangkut tentang sumber daya guru, jadwal kepala sekolah yang sifatnya mendadak dan rendahnya motivasi guru yang mendekati masa pensiun untuk melaksanakan tugasnya masing-masing.Kata Kunci: Strategi Kepala Sekolah, Supervisor dan Kompetensi Profesional Guru.